Vitamin K supports TGF-β1 depended in vitro human Langerhans cell differentiation and function via Axl - Bauer, Thomas; Richter-Eder, Susanne; Yasmin, Nighat; Jurkin, Jennifer; Köffel, René; Strobl, Herbert (Frontiers in Immunology, 2025)
IntroductionOn the outermost edge of the body a dense network of dendritic cells (DCs), the so-called Langerhans cells (LCs), represents the first immune barrier. The establishment and maintenance of this epidermal network is dependent on the cytokine transforming growth factor-β1 (TGF-β1) expressed by keratinocytes (KC) and LCs. We recently identified a crucial downstream effector of TGF-β1, the receptor tyrosine kinase Axl. Axl belongs to the TAM receptor family, which also includes Tyro3 and Mer, and is activated through the vitamin K-dependent ligands Gas6 and Protein S.MethodsWe have now established that TGF-β1 dependent in vitro human LC generation from CD34+ progenitor cells can be enhanced by Axl over-expression.ResultsAdditionally, we supplemented vitamin K into serum-free human LC generation cultures in order to activate the endogenous ligands Gas6 and Protein S. Vitamin K exhibited supportive effects on LC differentiation and LC-associated gene expression. The vitamin K antagonist warfarin on the other hand, hindered efficient LC differentiation. Blocking antibodies against Axl abrogated the positive effect of vitamin K on LC differentiation. Lastly, vitamin K downregulated the immune activation marker CD86 during LC differentiation and blocked the upregulation of CD86 during LC activation in vitro, in an Axl independent manner.DiscussionTaken together, we provide evidence for the supportive role of vitamin K in regulating skin immunity.